2017
DOI: 10.1038/srep39289
|View full text |Cite
|
Sign up to set email alerts
|

The autofluorescence characteristics of bacterial intracellular and extracellular substances during the operation of anammox reactor

Abstract: Anammox is a cost-effective process to treat nitrogenous wastewater. In this work, excitation–emission matrix (EEM) fluorescence spectroscopy was used to characterize the intracellular and extracellular substances of anammox sludge during reactor operation of 276 days. Four main fluorophores were identified from the intracellular substances. Two main protein-like fluorophores were identified from the extracellular substances. Correlation analysis revealed that intracellular 420 peak and humic-like peak had str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In the present study, we used the EEM to characterize the fluorescence fingerprints of seven oral microorganisms. Several other researchers have also used an EEM to characterize dissolved organic matter and intra‐/extracellular substances . Although the present study did not analyze the fluorescence spectrum by extracting the intracellular components, various signals appearing in the EEM were attributed to the various biomolecules of the cells based on previous studies .…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, we used the EEM to characterize the fluorescence fingerprints of seven oral microorganisms. Several other researchers have also used an EEM to characterize dissolved organic matter and intra‐/extracellular substances . Although the present study did not analyze the fluorescence spectrum by extracting the intracellular components, various signals appearing in the EEM were attributed to the various biomolecules of the cells based on previous studies .…”
Section: Discussionmentioning
confidence: 75%
“…We acknowledge that there are some limitations in this study. First, although vitamins (e.g., flavin), coenzymes (e.g., NADH), and lipofuscin pigments are suggested to be major sources of cellular autofluorescence (4), we have not analyzed which intracellular molecules characterize the innate fluorescence signatures that distinguish cell types. However, our results demonstrate the effectiveness of innate fluorescence signature analysis as a tool for predicting cell types and physiological status, independent of precise knowledge on how intracellular chemical compositions are mapped onto innate fluorescence signatures.…”
Section: Discussionmentioning
confidence: 99%
“…A cell’s innate fluorescence signature, an assemblage of autofluorescence signals emitted by diverse biomolecules within the cell (1), is known to reflect various cellular properties and physiological statuses. Previous studies have demonstrated that analysis of fluorescence signatures, for example, when coupled with a principal-component analysis (PCA), allows tag-free analysis of cell types and physiological status within live and intact microbial colonies, bulk microbial culture suspensions (2, 3), active sludges (4), mammalian tissues (5, 6), and mammalian cells (1, 7).…”
Section: Introductionmentioning
confidence: 99%
“…For example, although the introduction of Cu and OTC slightly reduced the heme c content due to deceleration of AnAOB growth rates, after long-term acclimation to the presence of Cu and OTC, the heme c content of an anammox reactor gradually elevated to 1.2-fold more than the initial content, implying the ability of AnAOB to grow normally under OTC + Cu stress with the help of acclimation (Zhang et al 2016b). Extracellular polymeric substances (EPS) secreted by microorganisms in response to harsh environmental stress chiefly comprised polysaccharides, proteins, humic acids, nucleic acids, and other organic macromolecules (Hou et al 2017), and can affect activated sludge properties (Sheng et al 2010). The characteristics and structures of these biomacromolecules are extremely complex owing to their different functional groups, including hydroxyl, carboxyl, phosphate groups, aldehyde, amide, and benzyl, which are likely to interact with each other and join these macromolecules, resulting in creating more intricate spatial structures (Jia et al 2017).…”
Section: Effect On Heme C and Eps Contentsmentioning
confidence: 99%